CHILD MORAL EDUCATION WITH PROJECT-BASED LEARNING IN CONTEXTUAL LIFE: PERSPECTIVES OF QS AL-ANAM 151-153 AT DHARMA WANITA KINDERGARTEN, NGRAMI NGANJUK - Maidatus Sa’diyah; Wawan Herry Setyawan; Karyoto Karyoto; Dwi Sisbiantoro (Program Studi PGSD Universitas Flores, 2023)
This study intends to investigate how the Pancasila Student Profile Project is being implemented at Dharma Wanita Kindergarten in Ngrami Nganjuk, East Java, to teach students how to make jumputan batik by the character development of QS. Al Anam 151-153. An ethnographic approach was employed in the descriptive qualitative research methodology. The P5 Jumputan Batik Shirt Implementation Process is the subject of the study. Observation and documentation are used to obtain data. The source triangulation technique is applied to ensure the data's veracity. The presentation, reduction, and conclusion are the first steps in the data analysis technique. The results of the research show that. The Nganjuk Dharma Wanita Kindergarten teacher memorized all the steps sequentially in six sessions. In addition, students can develop character dimensions, be tough and creative, fearless and demanding of piety. The character built is by the first dimension of the Pancasila Student profile, fear of God Almighty. It has a noble character that reflects students having good morals in communicating with God Almighty in line with the commands of QS. Al-Anam 151-153. The teacher offers several solutions to overcome these difficulties, including (1) Formation of heterogeneous groups so that students who understand the teacher's instructions can explain their groups to their members. (2) By adding lessons, teachers can help students complete assignments and projects and meet their needs by tracking student progress.